Long‐term effectiveness of a combined student—parent and a student‐only smoking prevention intervention among 7th grade school children in Berlin, Germany. (19th September 2016) - Krist, Lilian; Lotz, Fabian; Bürger, Christin; Ströbele‐Benschop, Nanette; Roll, Stephanie; Rieckmann, Nina; Müller‐Nordhorn, Jacqueline; Willich, Stefan N.; Müller‐Riemenschneider, Falk
Abstract: Background and aims: In Germany, the smoking prevalence among adolescents is among the highest in Europe. Our aim was to evaluate the long‐term effectiveness of a combined student–parent and a student‐only smoking prevention programme to reduce the smoking prevalence among 7th grade students in Berlin. Design: Three‐armed cluster‐randomized controlled trial (RCT). Schools as cluster units were randomized into (i) student intervention, (ii) combined student–parent intervention or (iii) control group, with follow‐up after 12 and 24 months. Setting: High schools and integrated secondary schools in Berlin, Germany. Participants: Seventh grade students aged 11–16 years. We included 47 schools, 161 classes and 2801 students [50.1% girls, mean age ± standard deviation (SD) = 13.0 ± 0.6 years]. Measurements: The primary outcome was self‐reported regular smoking (at least one cigarette per day) after 24 months (point prevalence). Further self‐reported outcomes were other smoking behaviours as well as parental rules and attitudes towards smoking. Comparisons were calculated as odds ratios (OR) with 95% confidence intervals (CI). Findings: At baseline, 2.3% of the students reported that they smoked regularly. After 24 months, 7.8% and 7.0% were regular smokers in the student–only intervention and the student–parent intervention, respectively, compared with 10.1% in the control group. The OR for being a regular smoker was 0.81 (0.34–1.92) for the student–parent intervention versus control, 0.95 (CI = 0.41–2.22) for the student‐only intervention versus control and 0.85 (0.38–1.89) for student–parent intervention versus student‐only intervention. Conclusion: A combined student–parent smoking prevention intervention delivered via secondary schools in Berlin, Germany did not result in a statistically significant reduction in regular smoking compared with a control group or a student‐only intervention. The student‐only intervention did not result in a significant reduction in regular smoking compared with the control group.